The challenges to control epilepsy in an isolated indigenous tribe in Brazil's Amazon: 15 years of follow-up - Honorato, Marcos Manoel; Cremaschi, Renata Carvalho; Coelho, Fernando Morgadinho Santos (Arquivos de Neuro-Psiquiatria, 2023)
Background Epilepsy is a common neurological disease that affects people all over the world, but it is rarely described in indigenous peoples.Objective To study the epilepsy characteristics and risk factors for seizure control in people from an isolated indigenous population.Methods This is a retrospective and historical cohort study conducted from 2003 to 2018 (15 years), at a neurology outpatient clinic, of 25 Waiwai tribes' indigenous individuals with epilepsy, inhabitants of an isolated forest reserve in the Amazon. Clinical aspects, background, comorbidities, exams, treatment, and response were studied. Factors that impacted seizure control over 24 months were identified using Kaplan-Meier curves and Cox and Weibull regression models.Results The majority of cases started in childhood, with no difference regarding gender. Focal epilepsies were predominant. Most patients had tonic-clonic seizures. A quarter of them had a family history, and 20% had referred febrile seizures. There was intellectual disability in 20% of patients. Neurological examination and psychomotor development were altered in one third of the participants. The treatment controlled 72% of the patients (monotherapy in 64%). Phenobarbital was the most prescribed anti-seizure medication, followed by carbamazepine and valproate. The most relevant factors that impacted seizure control over time were abnormal neurological exam and family history.Conclusion Family history and abnormal neurological exam were predicted risk factors for refractory epilepsy. Even in an isolated indigenous tribe, the partnership between the indigenous people and the multidisciplinary team ensured treatment adherence. The public healthcare system must guarantee modern anti-seizure medications, mainly for this vulnerable population, which has no other source of treatment.
Keywords: Epilepsy; Seizures; Indigenous Peoples; Amazonian Ecosystem